The Situation of Social Cooperatives in Small Villages in Hungary - Katalin Lipták (Administrative Sciences)
Social cooperatives, which are an important pillar of the solidarity economy, have become increasingly popular and common in Hungary over the past 10 years, especially in disadvantaged settlements, where the administrative burden of public employment is outsourced to social cooperatives. Analyzing social cooperatives in small villages is a relevant topic for local economic development. Of the 3155 settlements in Hungary, 1162 have a population of less than 500 inhabitants, i.e., small villages. In the spatial structure of Hungary, small villages tend to be located on the periphery, which is both the spatial and socio-economical peripheral position, with mostly disadvantaged inhabitants with low educational attainment and high unemployment. In these settlements, local communities can better understand what hinders and what helps their economies to grow and improve living standards by assessing their economic base. With this new knowledge, local communities can achieve results through strategically designed programs and projects that social cooperatives can join and help achieve. The methodology of the study is field research; we interviewed managers of the social cooperatives to learn about its operations and difficulties. The study described well-run and successful social cooperatives. In small villages, these cooperatives can be an important source of employment, even if the number of people employed is low. The experiences of the field research are presented in the form of recommendations for policymakers, as social cooperatives can be an important instrument of employment policy.